I want to be an astronaut - Grace, Catherine O'Neill, 1950-; Maze, Stephanie (San Diego : Harcourt Brace, 1997)
Describes what it is like to be an astronaut, some of the ways to prepare for this career, and the work in various related jobs.
"A Maze Productions.".
Includes bibliographical references.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
8.2
Keywords: Astronautics -- Juvenile literature; Astronautics -- Vocational guidance; Astronauts; Occupations; Vocational guidance; Astronautics -- Vocational guidance; Astronauts; Occupations; Vocational guidance